Analisis Tindak Aborsi Berdasarkan Perspektif Hukum Pidana dan Hukum Islam: Studi Kasus Putusan Perkara Nomor 288/Pid.Sus/2021/PN.Jkt.Tim dan Fatwa MUI Nomor 4 Tahun 2005) - Abduh, Syahidah; Amalia, Nurul; Bianda, Ryan (VISA: Journal of Vision and Ideas, 2025)
This research is motivated by the rampant practice of illegal abortion in Indonesia which is carried out without legal or sharia basis and weak public understanding. Previous studies tend to discuss aspects of criminal law or Islamic law separately, so this study seeks to present a comparative analysis of both. The goal is to review the act of abortion through Decision No. 288/Pid.Sus/2021/PN. Jkt.Team and Fatwa MUI No. 4 of 2005. The method used is normative qualitative research with literature study and juridical-comparative analysis. The results of the study showed that the defendant violated Article 75 jo. Article 194 of the Health Law and is not in accordance with the requirements of sharia. Criminal law emphasizes legal-formal aspects, while Islamic law emphasizes morality and the protection of the soul. The court decision has imposed a criminal sentence, but it has not presented substantive justice. This research emphasizes the need for an integrative legal approach involving education, social protection, and moral-religious considerations.